Passive edge tracing of deformable object by robot - Sahari K.S.M.; Seki H.; Kamiya Y.; Hikizu M. (Fuji Technology Press, 2023)
Usage of active tracing method to find a second corner has been proven to be efficient in finding a second corner next to the first found corner. Passive tracing is a method where the tracing gripper is static while another gripper holding the first corner maneuvers according to the feedback from sensors inside the static gripper so that it pulls the clothes appropriately for the static gripper, with adequate force control, to trace the edge of the clothes. Vision sensor is used from time to time to check whether the static gripper has reached the second corner or not.